The dimension of the join of two graphs - Gervacio, Severino V. (Animo Repository, 2005)
A graph is of dimension n if it can be drawn in then-dimensional Euclidian space Rn such that the edges are straight line segments of one unit long, but not in some Eucliclean space of lower dimension. A study has been made by Maehara on the dimension of the graph obtained from a complete graph after removing the edges of a disjoint family of complete subgraphs. This paper investigates the dimension of the join of two trees, a tree and a cycle, or two cycles.